The use of seedlings of multiple roots on the establishment of coffee plantation - Carvalho, Alex Mendonça de; Baliza, Danielle Pereira; Trevisan, Welington Lazaro; Guimarães, Rubens José; Ferreira, André Dominghetti (Coffee Science - ISSN 1984-3909, 1970)
Higher production of coffee plants (Coffea arabica L.), requires abundant and deeper roots, well branched and physiologically active. However, the root grow system is a complex process, which is affected by many factors. Thus, this work aimed at to study the influence of multiple roots in the initial growth of three coffee cultivars considering the presence and absence of mulch on the planting row. The experiment was carried out at the Paineira Farm in located in the district of Bom Jesus da Penha, MG - Brazil. The experimental design was randomized in blocks with factorial scheme (2 x 3 x 2) of two types of cuttings: single and multiple rooted seedlings, three cultivars: Paraíso MG 491-1, Catuaí Vermelho IAC 99 and Catucaí Amarelo 2SL and by the presence and absence of mulch on the planting row. The parameters evaluated were the plant height (cm), the stem base diameter (mm) and number of plagiotropic branches. The results showed that plants originated from single roots presented better development in the field during the establishment of the coffee plantation. The cultivar Catuaí IAC 99 was the most sensitive, presenting reductions in the growth of the plant height, stem base diameter and the plagiotropic branches number of 22.7%, 35.2% and 52.7% respectively, when multiple rooted seedlings were considered. The use of mulch during the establishment of the coffee plantation with multiple rooted seedlings increased the growth in height of 12.6% when compared with single rooted seedlings, however with lower emission of plagiotropic branches, which are decisive for future production.